2020
DOI: 10.1049/wss2.12006
|View full text |Cite
|
Sign up to set email alerts
|

Anchor selection by geometric dilution of precision for an indoor positioning system using ultra‐wide band technology

Abstract: In wireless localization systems, the performance enhancement of location estimation is an important goal. In recent years, different positioning systems using an ultra‐wide band (UWB) technology have been created, and always an evaluation metric to test such systems is needed for ensuring a suitable system for a specified application. Also, a non‐line‐of‐sight (NLOS) identification and mitigation method is needed usually when utilizing the UWB technology. The mean‐square‐error (MSE) and geometric dilution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This acquired result is far from typical, especially with UWB technology. [96] UWB --------------------√ LOS Only simulation is implemented in this approach in a test area over (15m×15m). The issue with this approach is that it is a complex metric in terms of matrix operation and needs a significant time to install.…”
Section: Complexit Ymentioning
confidence: 99%
“…This acquired result is far from typical, especially with UWB technology. [96] UWB --------------------√ LOS Only simulation is implemented in this approach in a test area over (15m×15m). The issue with this approach is that it is a complex metric in terms of matrix operation and needs a significant time to install.…”
Section: Complexit Ymentioning
confidence: 99%
“…Albaidhani proposed a novel positioning algorithm specifically tailored for indoor applications, which was evaluated using mean-square error (MSE) and dilution of precision (DOP) as criteria to optimize base station placement and improve positioning accuracy [20]. In one study, the accuracy factor was calculated and simulated under different numbers of pseudo-satellites, and the optimal observation matrix was determined by eigenvalue analysis, with a four-satellite layout identified as optimal [21].…”
Section: Introductionmentioning
confidence: 99%
“…Guo Y found that even if the ranging error is small, the localisation error is large in a narrow space, thus a localisation algorithm combining Kalman filtering (KF) and precision factor (DOP) is proposed to improve the accuracy and stability of localisation in a narrow space [13]. Albaidhani A proposed a positioning algorithm suitable for indoor use and tested the UWB positioning system under this algorithm using the values of the mean square error (MSE) and the factor of precision (DOP) to select the optimal base station placement and improve the positioning accuracy [14].The study by calculating and simulating the positioning accuracy factor under different numbers of pseudo-satellites, the optimal observation matrix was calculated using matrix eigenvalue analysis, and the four-satellite layout was calculated as the optimal observation matrix [15]. Taking different types of accuracy factors as the theoretical basis, he proposed the establishment of a four-dimensional model with altitude angle, azimuth angle and observation time as independent variables and relative accuracy factor as dependent variable to improve the accuracy of positioning and provide a guarantee for the optimal deployment of satellites [16].…”
Section: Introductionmentioning
confidence: 99%